2018
DOI: 10.1016/j.tranon.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ6 Promotes Lung Cancer Proliferation and Metastasis through Upregulation of IL-8–Mediated MAPK/ERK Signaling

Abstract: Lung cancer is notorious for high morbidity and mortality around the world. Interleukin (IL)-8, a proinflammatory chemokine with tumorigenic and proangiogenic effects, promotes lung cancer cells growth and migration and contributes to cell aggressive phenotypes. Integrin αvβ6 is a receptor of transmembrane heterodimeric cell surface adhesion, and its overexpression correlates with poor survival from non–small cell lung cancer. However, the cross talk between αvβ6 and IL-8 in lung cancer has not been characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Integrin αvβ3, as an important cell surface adhesion molecule, has also been reported to be overexpressed in cancer tissues and mediate the invasion and metastasis of HCC cells [1316]. Increasing evidence suggests that the close relationship between IL-8 and integrin is critical for cancer progression [18, 19, 21, 22]. To explore the role of IL-8 and integrin αvβ3 in HCC metastasis, we detected the expression of IL-8, integrin αv and integrin β3 in several HCC cell lines with different metastatic potential, and found that both protein expression and mRNA levels of IL-8, integrin αv, and integrin β3 were significantly increased in highly metastatic HCC cell lines (HCCLM3 and MHCC97H) compared with low metastatic cell lines (Huh-7 and HepG2).…”
Section: Discussionmentioning
confidence: 99%
“…Integrin αvβ3, as an important cell surface adhesion molecule, has also been reported to be overexpressed in cancer tissues and mediate the invasion and metastasis of HCC cells [1316]. Increasing evidence suggests that the close relationship between IL-8 and integrin is critical for cancer progression [18, 19, 21, 22]. To explore the role of IL-8 and integrin αvβ3 in HCC metastasis, we detected the expression of IL-8, integrin αv and integrin β3 in several HCC cell lines with different metastatic potential, and found that both protein expression and mRNA levels of IL-8, integrin αv, and integrin β3 were significantly increased in highly metastatic HCC cell lines (HCCLM3 and MHCC97H) compared with low metastatic cell lines (Huh-7 and HepG2).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-8 acts as a chemoattractant for neutrophils and myeloid-derived suppressor cells and thereby contributes to the immunosuppressive nature of the tumor microenvironment. In addition, expression of IL-8 correlates with that of the αvβ6 integrin in colorectal and lung cancer disease states in which these two molecules interact to promote tumor cell proliferation and migration [37,38]. Interleukin-8 belongs to the cysteine-amino acid-cysteine (CXC) family of chemokines and, along with CXCL6, is a ligand for CXCR1.…”
Section: Introductionmentioning
confidence: 99%
“…For example, integrin β1 is a member of the β sub-family, which forms dimers with different α subunits (α1, α2, α3, α4, α5, α6, α7, and αV). Integrin β1 (ITGB1) has vital roles in growth and motility in breast cancer, non-small cell lung cancer, gastric cancer, and liver cancer [ 16 , 17 ]. In esophageal squamous cell carcinoma (ESCC), integrin α6β1and α6β4 are preferentially located at the invasive front of tumor mass as compared to the normal epithelium, and this change is positively correlated with tumor progression [ 18 ].…”
Section: Introductionmentioning
confidence: 99%